On T2 magnetic resonance and cardiac iron - Carpenter, John-Paul; He, Taigang; Kirk, Paul; Roughton, Michael; Anderson, Lisa J; de Noronha, Sofia V; Sheppard, Mary N; Porter, John B; Walker, J Malcolm; Wood, John C; Galanello, Renzo; Forni, Gianluca; et al. (Circulation (New York, N.Y.), 2011)
Measurement of myocardial iron is key to the clinical management of patients at risk of siderotic cardiomyopathy. The cardiovascular magnetic resonance relaxation parameter R2* (assessed clinically via its reciprocal, T2*) measured in the ventricular septum is used to assess cardiac iron, but iron calibration and distribution data in humans are limited. Twelve human hearts were studied from transfusion-dependent patients after either death (heart failure, n=7; stroke, n=1) or transplantation for end-stage heart failure (n=4). After cardiovascular magnetic resonance R2* measurement, tissue iron concentration was measured in multiple samples of each heart with inductively coupled plasma atomic emission spectroscopy. Iron distribution throughout the heart showed no systematic variation between segments, but epicardial iron concentration was higher than in the endocardium. The mean ± SD global myocardial iron causing severe heart failure in 10 patients was 5.98 ± 2.42 mg/g dry weight (range, 3.19 to 9.50 mg/g), but in 1 outlier case of heart failure was 25.9 mg/g dry weight. Myocardial ln[R2*] was strongly linearly correlated with ln[Fe] (R²=0.910, P<0.001), leading to [Fe]=45.0×(T2*)⁻¹·²² for the clinical calibration equation with [Fe] in milligrams per gram dry weight and T2* in milliseconds. Midventricular septal iron concentration and R2* were both highly representative of mean global myocardial iron. These data detail the iron distribution throughout the heart in iron overload and provide calibration in humans for cardiovascular magnetic resonance R2* against myocardial iron concentration. The iron values are of considerable interest in terms of the level of cardiac iron associated with iron-related death and indicate that the heart is more sensitive to iron loading than the liver. The results also validate the current clinical practice of monitoring cardiac iron in vivo by cardiovascular magnetic resonance of the midseptum.